Parental Deception: Perceived Effects on Parent-Child Relationships. (6th February 2017) - Cargill, Joscelyn R.; Curtis, Drew A.
Abstract : Deception research has recently begun to examine its occurrence within parent-child relationships. The use and consequence of parental deception on the parent-child relationship remains unclear. The current study examined the effects of parental lies on the parent-child relationship. Questionnaires were provided to 276 participants that asked them to indicate their satisfaction with their parents, what kinds of lies parents have told, the seriousness of the lies, and how the lies affected their relationship. Findings revealed a negative correlation between parental deception and satisfaction, and parents were rated most likely to use white lies than any other types. The implications of the use of deception within parent-child relationships are discussed.